Da'wah Strategy of the Tabligh Majelis Of Muhammadiyah Padang Sidempuan Regional Leadership in Fostering Religious Harmony - Harahap, Rizky Fadli; Soiman, Soiman (JASNA : Journal For Aswaja Studies, 2024)
This research is entitled "Da'wah Strategy of the Padang Sidimpuan Muhammadiyah Regional Leadership Tabligh Council in Fostering Religious Harmony." The aim of this research is to determine the state of religious harmony in the city of Padang Sidimpuan, the da'wah strategy of the Tabligh assembly of the Muhammadiyah regional leadership in Padang Sidimpuan City in improving the development of religious harmony in Padang Sidimpuan City, as well as supporting factors and factors inhibiting religious harmony in the city of Padang Sidimpuan. In this research, the researcher uses a qualitative methodology with a descriptive approach. Data collection techniques in this research are observation, interviews, and documentation. The location of this study was carried out at the Regional Muhammadiyah Leadership office in Padang Sidimpuan City, at the Majelis Ulama Indonesia Padang Sidimpuan office, and at the office of the Padang Sidimpuan Religion Ministry. The results of this research are: 1) The state of religious harmony in the city of Padang Sidimpuan can actually be said to be good; there is no misunderstanding or a high level of tolerance because the people in the city of Padang Sidimpuan generally still have unity in creating a harmonious society. in everyday life. 2) Supporting and inhibiting factors are (a) the existence of awareness of religious communities, a sense of kinship, and religious tolerance, thereby creating a sense of equality and harmony among religious communities in the city of Padang Sidimpuan, and (b) frequent events that occur to create harmony among religious communities. In the city of Padang Sidimpuan, there was a misunderstanding caused by a third party (an outside party). So that, with this research, the Tablighi assembly's Islamic da'wah will continue to develop and be able to overcome similar factors that will occur in the future.